The mediating role of positive orientation in the relationship between personality traits and attitudes towards artificial intelligence - Wiesław Talik (PLoS ONE, 2026)
This study examines the mediating role of the positive orientation relationship between personality traits (extraversion, neuroticism, openness to experience, agreeableness, and conscientiousness) and attitudes towards artificial intelligence. The study was conducted in Poland with a sample of N = 922 adults. The research employed the Artificial Intelligence Attitude Scale (AIAS-4) , the Ten Item Personality Inventory (TIPI) and the Positivity Scale. The mediating effect of positive orientation on the relationship between personality traits and attitudes towards artificial intelligence was partially confirmed. The findings indicate that Big Five personality traits (with the exception of openness to experience) may lead to more positive attitudes towards AI and that this relationship is mediated by positive orientation. This research elucidates the mediating role of positive orientation, thereby contributing to a deeper understanding of the psychological processes driving individuals’ attitudes towards AI. The insights gained can inform policymakers, technologists, and practitioners aiming to promote the widespread acceptance and adoption of AI technologies in society.